Can Pahl and Beitz' systematic approach be a predictive model of designing?. (4th December 2017) - Kannengiesser, Udo; Gero, John S.
Abstract : Pahl and Beitz' 'Systematic Approach' is generally seen as a prescriptive model of designing based on observations of professional design practice. In this paper, we examine whether this model can be used as a predictive model. This is done by testing its predictive capacity for the design behaviour of students that are formally taught design and design methods. The behavioural observations used in this study are based on protocols of 15 design sessions involving mechanical engineering students after their first year of design education and 31 design sessions of the students using various concept generation methods. The design protocols and the Systematic Approach are coded uniformly using the Function–Behaviour–Structure (FBS) design issue schema. Cumulative occurrence analysis is used to derive qualitative and quantitative measures as a basis for comparison between the Systematic Approach's prediction and the students' design behaviour. The results indicate that the Systematic Approach can predict some but not all of students' design issue behaviour.